Características de los accidentes laborales producidos por pinchazo de aguja y objetos punzocortantes en el personal de salud del Hospital II-2 Tarapoto, periodo agosto – noviembre del 2016 - Del Aguila Calderon, Karen Patricia (2016)
Objective: To know the characteristics of occupational accidents caused by needle stick and sharp objects in the health personnel of Tarapoto II-2 Hospital, from August to November, 2016. Methodology: A descriptive, relational, cross-sectional study. From a population of 388 health workers, a sample of 142 was obtained. Data collection was by individual interview with a questionnaire as an instrument. Results: A frequency of 65.5%, predominantly female, was found between 18 and 26 years, nurses, between 6 and 10 years of working age, and surgical areas. There is no relation between the epidemiological characteristics and the occurrence of accidents (p˃α = 0.05). 47.3% experienced at least one accident. 67.8% had injuries after the second year of service and 46.2% did in morning shift. The hollow needle caused 69.9% of accidents and in 50.5% the device was contaminated with blood. During the procedure 33.3% of the accidents were presented and only 39.8% were reported. 60.7% did not report because they did not believe they had an exposure infection. Only 32.3% sought medical care, of which 73.3% did so immediately. Conclusion: A large percentage of health personnel have experienced injury during their work performance